Porod z uporabo epiduralne analgezije ali kombinirane spinalno-epiduralne analgezije - Zakšek, Teja (Obzornik zdravstvene nege, 2011)
A number of pain relief methods are presently available to birthing woman among which epidural analgesia or combined spinal epidural analgesia have proved to be the most effective labor-pain management option. The article aimsto present the role of midwives in caring for women who are supported by epidural analgesia during labour in the Hospital Postojna. Methods: A descriptive research method was used to delineate the procedure of epidural analgesia provided for labour and delivery. The results of the relevant literature justifying the method of administration are presented. Discussion and conclusions: In the first stage of birth, epidural analgesia or combined spinal epidural analgesia should be administered at the proper time. A midwifehas to ensure that a labouring woman regularly changes the position. Since the second stage of labor is usually prolonged, a midwife should wait till the baby lowers deep into the pelvis and nestles into position for birth.Epidural analgesia does not prolong the third stage of labour. Today women have the possibility to opt for epidural analgesia or spinal epidural analgesia as a form of labor pain relief. As more parturients demand pain-freelabor, it is important that midwives managing labour have a clear understanding of the benefits, contraindications and risks of epidural analgesia and respond to the specific needs of women.
Keywords: Analgesia, Epidural; Analgezija epiduralna; Babice; babištvo; Blennioidei; Bolečina; childbirth; epiduralna analgezija; Hospitals, Maternity; Labor; midwifery; Nurse Midwives; Pain; Porod; Porodnišnice